2000
DOI: 10.1636/0161-8202(2000)028[0169:tiohfo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Habitat Features on Web Features and Prey Capture of Argiope Aurantia (Araneae, Araneidae)

Abstract: Prey capture by the orb=web spider, Argiope aurantia Lucas 1833, depends on the type of the web=site selected. I analyzed A. aurantia web sites in open field and adjacent forest edge habitats to identify habitat features associated with web characteristics and prey capture. In the open field, the use of herbs or grass for web attachment was associated with smaller web diameters, and lower attachment heights and web heights. In both forest edge and open field, the distance to the nearest flower was less when we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…However, some of the species studied here (e.g. Nephila, Argiope) are known to capture large lepidopterans, hymenopterans, orthopterans, and other high kinetic-energy insects (Robinson and Robinson, '70;Howell and Ellender, '84;Foelix, '96;McReynolds, 2000;Blackledge and Zevenbergen, 2006). Capture of these large, energetically rewarding, but also rare, insects is in fact crucial for the effective reproduction of orb-weaving spiders (Venner and Casas, 2005).…”
Section: Performance and Ecologymentioning
confidence: 96%
See 2 more Smart Citations
“…However, some of the species studied here (e.g. Nephila, Argiope) are known to capture large lepidopterans, hymenopterans, orthopterans, and other high kinetic-energy insects (Robinson and Robinson, '70;Howell and Ellender, '84;Foelix, '96;McReynolds, 2000;Blackledge and Zevenbergen, 2006). Capture of these large, energetically rewarding, but also rare, insects is in fact crucial for the effective reproduction of orb-weaving spiders (Venner and Casas, 2005).…”
Section: Performance and Ecologymentioning
confidence: 96%
“…Additionally, several studies suggest that there is variation in the performance properties of capture spiral silk across species (Craig, '87;Bond and Opell, '98;Bond, 2000, 2001). Finally, according to extensive research on spider foraging ecology, the webs of different spider species capture different sets of insect prey (Robinson and Robinson, '70;Howell and Ellender, '84;Craig, '87;Uetz and Hartsock, '87;Bishop and Connolly, '92;Miyashita, '97;McReynolds, 2000). It is largely unknown how fibroin sequence variation might affect the material properties of capture silks and how silk properties might be adapted for capturing different types of insects.…”
Section: Spider Capture Silk Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are taller and they have more horizontal plant components. Shrub height has been associated with differences in spider community composition (Hatley & MacMahon 1980;Abraham 1983;Greenstone 1984;Döbel et al 1990;Gibson et al 1992 ;Lubin et al 1993;Ward & Lubin 1993;Aiken & Coyle 2000;McReynolds 2000). Robinson (1981) used simple models to demonstrate that vertical/horizontal orientation affected the distribution of certain spider species.…”
mentioning
confidence: 99%
“…Previously it had been suggested that individuals building webs higher up in less dense vegetation could intercept larger flying prey (Brown 1981; but see Enders 1976); however, prey capture rate has also been shown to be unaffected by web height and that spiders do not change web height according to prey abundance (Herberstein 1997, Herberstein 2000, Prokop and Gryglakova 2005. It is likely that either small increases in web height (only 10 cm or so) at the juvenile stage do not affect the type of prey caught, or web height is the result of available abiotic factors and seasonal growth only, and has little effect on prey capture (Herberstein 1997, McReynolds 2000. A recent study found that plant species composition best predicts the nature of arthropod assemblages, and that vegetation structure is much less important (Schaffers et al 2008).…”
Section: Discussionmentioning
confidence: 99%